STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TECHNIQUE TOWARDS STUDENTSâ SELF-EFFICACY IN READING - Asnan, NurÃ¢Â€Â™amila Sholiha (IKIP Mataram, 2016)
This study is generally attempted to find out The Effects of Student Team Achievement Division (STAD) Technique towards Studentsâ Self-Efficacy In Reading for the first grade students at SMA Darun Najihin NW Bagik Nyala. The method of this research is experimental research. The population of this research was the first grade students of SMA Darun Najihin NW Bagik Nyala in academic year 2016/2017. The sample of the study was 54 students consist of two classes, experimental class and control class. The technique used to analysis the data was test formula. From the research data found out that the studentsâ t-test score (2,58) and t-table (1,679) from (df) was 52. Based on the result of the study and the correlation between self-efficacy and reading was r-test (0,604) > r-table (0,268). It can be concluded that, the use of STAD has positive effect toward studentsâ self-efficacy in reading and has correlation both of them at the first grade students of SMA Darun Najihin NW Bagik Nyala in academic year 2016/2017.